Mixing viscoplastic fluids in stirred vessels over multiple scales: A combined experimental and CFD approach. (23rd November 2019) - Russell, Andrew W.; Kahouadji, Lyes; Mirpuri, Karan; Quarmby, Andrew; Piccione, Patrick M.; Matar, Omar K.; Luckham, Paul F.; Markides, Christos N.
Highlights: Viscoplastic flows were characterised in vessels equipped with Rushton turbines. A range of scales and rheological properties were investigated. A scaling method for matching dimensionless cavern sizes was proposed. Flows from pitched-blade turbine and Rushton turbine agitation were compared. Abstract: Dye visualisation techniques and CFD are used to characterise the flow of viscoplastic Carbopol™ solutions in stirred vessel systems over multiple scales. Centrally-mounted, geometrically-similar Rushton turbine (RT) impellers are used to agitate various Carbopol 980 (C980) fluids. The dimensionless cavern diameters, Dc / D, are scaled against a combination of dimensionless parameters: Rem −0.3 Rey 0.6 n − 0.1 ks −1, where Rem, Rey, n and ks are the modified power-law Reynolds number, yield stress Reynolds number, flow behaviour index and impeller geometry constant, respectively. Excellent collapse of the data is demonstrated for the fluids and range of flows investigated. Additional data are collected using a pitched-blade turbine (PBT) with cavern size similarity being shown between the RT and PBT datasets. These results are important in the context of scale-up/scale-down mixing processes in stirred vessels containing complex fluids and can be used to show that flow similarity can be achieved in these systems if the processes are scaled appropriately.